Knowledge and Practice of Food Hygiene among Women Accommodated in Flood Displaced Person’s Camps in Bayelsa State - Walker, Doubrapade (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The 2022 flood caused a massive destruction of property worth millions of naira, loss of human lives, and displaced millions of persons who mostly stayed in flood displaced person’s camps (FDP) that do not have basic amenities. The insanitary condition of these camps make them a perfect avenue for the spread of water-borne and food-borne diseases. To curtail the spread of these infectious diseases in any community, basic food hygiene principles must be understood and observed by individuals and families in the population. The study assessed knowledge and practice of food hygiene among women accommodated in flood displaced person’s camps in Bayelsa State. The study adopted cross-sectional survey design. All the 275 women that were accommodated in the three FDP camps in Bayelsa State formed the population of the study. This instrument for data collection was a self-developed questionnaire titled Knowledge and Practice of Food Hygiene among Women accommodated in Flood Displaced Person’s Camps questionnaire (KPFHWAFDPC) with three sections. A reliability coefficient of 0.84 was established through the split-half method. Data obtained were coded into software package for social science (SPSS-IBM) and analyzed using frequency and percentage for the research questions and chi-square the hypothesis. The hypothesis was tested using chi-square, set at 0.05 level of significance. The results revealed that, majority of the respondents had both poor knowledge (77.5) and practice (84.2) of food hygiene. There was a significant difference in the practice of food hygiene among flood displaced women in Bayelsa State in relation to education level. The author recommended that relevant stakeholders in the health sector should carry out intensive public awareness programmes on food hygiene principles at the grassroots level using appropriate channels of communication.